Entendendo os negócios com impacto social : uma análise dos elementos constituintes do modelo de negócio - Scherer, Patrícia Cristina (2014)
Social impact business are cost effective initiatives that address the needs of lowincome people by providing them with the access to quality products and services at affordable prices, as well as employment and income opportunities. This study aims at contributing to the understanding of this business model that has been getting increasingly more relevant in both the academic and corporate fields. The analysis of the theoretical groundwork indicated that the concept of social impact business does not come from a homogeneous perspective. An analytical framework to identify the elements that constitute the business social impact was proposed based on the characteristics found in the literature review. The methodology applied was of qualitative-quantitative, exploratory nature. As the procedure required for data collection, three steps were followed: a documental analysis using secondary data, interviews and surveys. The results from the data collection allowed us to identify the constituent elements of the business model, mapping existing initiatives in Brazil and describe their characteristics from the proposed framework for analysis, and assess the social impact of these initiatives.